2016
DOI: 10.1371/journal.pone.0151946
|View full text |Cite
|
Sign up to set email alerts
|

HIV, HBV and HCV Coinfection Prevalence in Iran - A Systematic Review and Meta-Analysis

Abstract: Backgroundworldwide, hepatitis C and B virus infections (HCV and HCV), are the two most common coinfections with human immunodeficiency virus (HIV) and has become a major threat to the survival of HIV-infected persons. The review aimed to estimate the prevalence of HIV, HBV, HCV, HIV/HCV and HIV/HBV and triple coinfections in different subpopulations in Iran.MethodFollowing PRISMA guidelines, we conducted a systematic review and meta-analysis of reports on prevalence of HIV, HBV, HCV and HIV coinfections in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
66
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 23 publications
9
66
1
1
Order By: Relevance
“…A recent national estimate of HCV prevalence among PWID was 51.46% (95% CI, 34.30 -68.62) (31). In the present study, we found an HCV antibody prevalence of 54.8% (95% CI, 50.8 to 58.7) in the PWID samples.…”
Section: Prevalence Of Hcv Antibodiessupporting
confidence: 62%
“…A recent national estimate of HCV prevalence among PWID was 51.46% (95% CI, 34.30 -68.62) (31). In the present study, we found an HCV antibody prevalence of 54.8% (95% CI, 50.8 to 58.7) in the PWID samples.…”
Section: Prevalence Of Hcv Antibodiessupporting
confidence: 62%
“…Patients who received multiple transfusions (PWRMT) and prisoners had a low prevalence as 0.01% and 0.28%, not statistically different from the prevalence in the general population. Those finding were similarly this study which found 0.26% of triple co-infections in MSM group, but they found in people who inject drug (Fahimeh, 2016).…”
Section: Discussionsupporting
confidence: 82%
“…The attributed effects of risk factors vary across different regions, depending on the epidemiologic distribution and prevalence of the risk factors in each region (25,27,30,(36)(37)(38). In the United States, Europe, and Japan, 22% of the cases of primary liver cancer are attributed to hepatitis B, while 60% are attributed to hepatitis C, and 43% are attributed to alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%